Induction

The proofs we've seen so far are examples of one type of proof, the direct proof. We now introduce another type of proof, the indirect proof. Indirect proofs come in several variants. One such variant is the proof-by-contradiction.

Proof-by-contradiction

In a proof-by-contradiction, we start by assuming that the opposite of what we are trying to prove (the negation) is true. Then, following this assumption, we take logical deductions until we arrive at a contradiction (a proposition that states "false equals true"). If we ever reach a false-equals-true, then that means that what we assumed from the very beginning was wrong. In other words, the opposite (the negation) cannot be true. And since the negation cannot be true, the original proposition must be true. More formally:

To prove a proposition P{P} is true, we assume that P{P} is false (¬P{\neg P} is true). From this hypothesis (P{P} is false), we prove that a falsehood is true (P{P} is false implies P{P} is true). In doing so, we prove that it must be the case that P{P} is true.

This works because if we can prove that ¬PF,{\neg P \nc F,} then the only way for ¬PF{\neg P \nc F} to be true is if ¬P{\neg P} is false. And if ¬P{\neg P} is false, then P{P} is true.

Example: Prove that 2{\sqrt{2}} is irrational. First, let's be clear about what our terms mean. An irrational number is a number that cannot be written as the ratio of two integers. In contrast, a rational number is a number that can be written as the ratio of two integers.

When we write a proof by contradiction, we always start by indicating that the proof is a proof by contradiction.

Assume for the purpose of contradiction that 2{\sqrt{2}} is a rational number. If 2{\sqrt{2}} is rational, then 2=ab{\sqrt{2} = \dfrac{a}{b}} where a{a} and b{b} are integers, and ab{\dfrac{a}{b}} is a fraction expressed in lowest terms (a fraction with no common divisors).

Squaring both sides: 2=a2b2.{2 = \dfrac{a^2}{b^2}.} Multiplying both sides by b2,{b^2,} we obtain 2b2=a2.{2b^2 = a^2.} This implies that a2{a^2} is even, since 2b2{2b^2} can be written as 2k{2k} given that b{b} is an integer. Because a2{a^2} is even, then it must be true that a{a} is even (since the square of an even number is even) — (2  a){(2 \space\vert\space a)} ("two divides a{a}").

Given that a{a} is even, a2{a^2} is a multiple of 4 — (4  a2).{(4 \space\vert\space a^2).} This means that (4  2b2).{(4 \space\vert\space 2b^2).} Dividing each side by 2, (2  b2).{(2 \space\vert\space b^2).}

Now, if 2 divides by b2,{b^2,} then it must be the case that b{b} is even. We've arrived at a contradiction. If a{a} is even and b{b} is even, then ab{\dfrac{a}{b}} is not a fraction in lowest terms. This means that 2{\sqrt{2}} cannot be rational, so it must be irrational. {\blacksquare}

The proof above was first discovered by a religious society of ancient Greece called the Pythagoreans. In ancient Greece, the practice of mathematics was a religious exercise. The ancient Greeks believed that mathematics was ruled by two gods — Apeiron and Peras. Apeiron was viewed as a malevolent god: the embodiment of primal chaos, the god of the infinite. In contrast, Peras was viewed as the benevolent one: the embodiment of order, the god of the finite.

One of the axioms of these mathematical mystics was that there were no irrational numbers — they simply did not exist. The Greeks denied their existence because they were evil; they were infinite. In contrast, the mystics affirmed the existence of the rational numbers because they were finite.

This denial of the infinite extended to other spheres. Every line, according to the Pythagoreans, was finite. From this axiom, they derived what we now know as the Pythagorean Theorem. If there was a triangle with legs of length 1, then the length of the hypotenuse was 2.{\sqrt{2}.} Because they denied the existence of the irrationals, the Pythagoreans constructed a theorem that 2{\sqrt{2}} was rational. Eventually, the Pythagoreans discovered the proof above.

Needless to say, this caused mayhem. The Pythagoreans were now confronted with the fact that their axioms were inconsistent. Every theorem they had proven was premised on the non-existence of irrationals, and they now had just found an irrational. The solution: Cover it up. According to legend, the Pythagoreans not only denied the result, they went so far as to murder the member who discovered the proof.

The Well-Ordering Principle

The Well-ordering Principle states:

definition. Every nonempty set of nonnegative integers has a smallest element.

This short statement contains numerous implications. First, it's false for the empty set ,{\emptyset,} since the empty set contains no elements. Second, it's false for the negative integers. And since it's false for the negative integers, it's false for the set of all integers. I.e., Z{\uint} is not well ordered. And since it's false for Z,{\uint,} it's false for the set of all rational numbers, Q.{\mathbb{Q}.} And since it's false for Q,{\mathbb{Q},} it's false for the set of all real numbers, R.{\reals.} These all imply that there's something very special about the nonnegative integers, a.k.a. the natural numbers N.{\nat.}1

The well-ordering principle allows us to construct numerous proofs-by-contradiction, and it is a cornerstone of proof-by-induction. For example, recall the proof that 2{\sqrt{2}} is irrational. In the previous proof, we used a little number theory and algebraic manipulation to construct a proof-by-contradiction. In that proof, however, we relied on a particular postulate:

Postulate. Let m,nZ+.{m, n \in \uint^{+}.} Then mn{\dfrac{m}{n}} can be written in lowest terms. In other words, mn{\dfrac{m}{n}} cannot be written as mn,{\dfrac{m'}{n'},} where m{m'} and n{n'} are positive integers with no common prime factors.

How do we know that this postulate is true? Well, we can prove it with WOP:

Proof (By Contradiction). Let m,nZ+.{m, n \in \uint^{+}.} Suppose mn{\dfrac{m}{n}} cannot be written in lowest terms. Further suppose that A{A} is the set of all positive integers that are numerators of mn.{\dfrac{m}{n}.} In other words, mA.{m \in A.} Because mA,{m \in A,} A{A} is nonempty.

Since A{A} is nonempty and AN,{A \subseteq \nat,} then by the well-ordering principle, A{A} contains a smallest integer m0A.{m_0 \in A.} Hence, again by WOP there exists an integer n0>0{n_0 > 0} such that:

m0n0 \dfrac{m_0}{n_0}

cannot be written in lowest terms.

Because m0n0{\dfrac{m_0}{n_0}} cannot be written in lowest terms, m0{m_0} and n0{n_0} must have a common prime factor, p>1.{p > 1.} Thus:

m0n0=m0/pn0/p \dfrac{m_0}{n_0} = \dfrac{m_0/p}{n_0/p}

This implies that m0/pn0/p{\dfrac{m_0/p}{n_0/p}} cannot be written in lowest terms either. Because A{A} is the set of all positive integers that are numerators of mn,{\dfrac{m}{n},} the numerator m0p{\dfrac{m_0}{p}} is a member of A.{A.} But m0/p<m0.{m_0 / p < m_0.} This contradicts the fact that m0{m_0} is the smallest element of A.{A.}

Since the assumption that C{C} leads to a contradiction, it follows that C{C} must be empty. And because C{C} must be empty, for all positive integers, the fraction mn{\dfrac{m}{n}} that can be written in lowest terms. {\blacksquare}

Proof-by-induction

We now turn to another variety of proofs — proof-by-induction. The concept of induction is actually a predicate itself:

Axiom. Let P(n){P(n)} be a predicate. If P(0){P(0)} is true, and nN:(P(n)P(n+1)){\forall n \in \nat : (P(n) \nc P(n + 1))} is true, then nN:P(n){\forall n \in \nat : P(n)} is true.

Another way of expressing the axiom above: If P(0){P(0)} is true, and if P(0)P(1),{P(0) \nc P(1),} and if P(1)P(2),{P(1) \nc P(2),} all the way up to P(n),{P(n),} then P(n){P(n)} is true for any natural number n.{n.} As an axiom, induction is relatively straightforward. If know that P(0){P(0)} is true, and we know that P(0)P(1),{P(0) \nc P(1),} and P(1)P(2),{P(1) \nc P(2),} all the way up to P(n),{P(n),} then it makes sense for P(n){P(n)} to be true for all n.{n.} We can think of this as akin to dominoes falling.

Of note, mathematical induction is not a form of inductive reasoning. In inductive reasoning, we reason that because of some previously observed phenomenon, we can make inferences about the future. This is entirely unrelated to mathematical induction. Mathematical induction is, in fact, a form of deductive reasoning, not inductive reasoning. In other words, mathematical induction is to induction what Rocky Mountain oysters are to oysters. Similar names but very, very different things. When mathematicians use the word "induction" alone, they are referring to the mathematical, rather than epistemic, context.

Let's see an example. Prove the following:

nN,{\forall n \in \nat,}

1+2+3++n=n(n+1)2 1 + 2 + 3 + \ldots + n = \dfrac{n(n + 1)}{2}

Note that the ellipses, ,{\ldots,} tells us that we must complete the pattern. In this case, there is a pattern to 1+2+3++n.{1 + 2 + 3 + \ldots + n.} In this case, each element in the sequence is an increment-by-one of the element before it. Because this can be very vague, we have several ways to express this idea more explicitly.

i=1ni=1ini=1ini \sum_{i = 1}^{n} i = \sum_{}^{1 \leq i \leq n} i = \sum_{1 \leq i \leq n}^{} i

In each of the notations above, we are expressing the clause, "The sum of i{i} from i=1{i = 1} to i=n.{i = n.} Thus, the proposition we are asked to prove can be more succinctly expressed as:

nN:(i=1n=n(n+1)2) \forall n \in \nat : \left(\sum_{i = 1}^{n} = \dfrac{n(n + 1)}{2}\right)

The notation above is called a summation. There are a number of reasons why use the summation notation. To begin with, if n=1,{n = 1,} then the expression 1+2++n{1 + 2 + \ldots + n} is ambiguous and confusing. With the summation notation, we can simply say the when n=1,{n = 1,} then i=1n=1,{\sum_{i = 1}^{n} = 1,} since the sum of 1 to 1 is simply 1. Similarly, if n0,{n \leq 0,} then i=1n=0.{\sum_{i = 1}^{n} = 0.} Why? Because there are no numbers to sum. We call these two cases, n=0{n = 0} and n=1,{n = 1,} the edge cases.

All this in mind, let us write the proof. The first thing we do is to state that the proof will be done by induction. Next step: What is our predicate? In other words, what is the hypothesis? Here, it is the proposition we are trying to prove: That i=1n=n(n+1)2.{\sum_{i = 1}^{n} = \dfrac{n(n + 1)}{2}.}

Proof (by induction).

Let P(n){P(n)} be the proposition that i=1n=n(n+1)2.{\sum_{i = 1}^{n} = \dfrac{n(n + 1)}{2}.}

Now we begin thinking about the proof. The first thing to analyze is the base case. Here, we must establish that P(0){P(0)} is true. We saw this earlier. The sum of i=1{i = 1} to 0 of i{i} is 0. The proposition is also true by algebra:

i=10=0(0+1)2=0 \sum_{i = 1}^{0} = \dfrac{0(0 + 1)}{2} = 0

Having proved the base case is true, we now must prove the second part, the inductive case. In this case, we must show: For n0,{n \geq 0,} P(n)P(n+1){P(n) \nc P(n + 1)} is true.

Now, recall basic logic. How do we show that an implication is true? There is only one situation where the implication is false, and that is when P(n){P(n)} is true and P(n+1){P(n + 1)} is false. Thus, to prove this implication, we must assume that P(n){P(n)} is true, then determine whether P(n+1){P(n + 1)} is true. So, putting together what we have so far:

Let P(n){P(n)} be the proposition that i=1n=n(n+1)2.{\sum_{i = 1}^{n} = \dfrac{n(n + 1)}{2}.} When n=0,{n = 0,} then i=10=0.{\sum_{i = 1}^{0} = 0.} This is the base case. We now prove the inductive case: For n0,{n \geq 0,} P(n)P(n+1).{P(n) \nc P(n + 1).}

Assume P(n){P(n)} is true for purposes of induction. Following this assumption, we must prove that i=1n+1=(n+1)(n+2)2.{\sum_{i = 1}^{n + 1} = \dfrac{(n + 1)(n + 2)}{2}.}

The last sentence above is arguably the most confusing for non-mathematician readers. It seems as if in trying to prove P(n),{P(n),} we are assuming P(n).{P(n).} Isn't this circular? Admittedly, it appears to teeter very close. In actuality, it is not at all circular. We are assuming P(n){P(n)} to prove the necessary condition of the proposition P(n)P(n+1).{P(n) \nc P(n + 1).} Remember, in mathematics, we write a proof one step at a time, from one deduction to the next.

We should also be very clear about what we mean when we say something like "Assume x.{x.}" We are not saying that x{x} is, in fact, true. We are saying, "Just pretend for a moment—for the sake of a hypothetical—that x{x} is true." The only purpose of an "Assume x{x}" statement is to obtain a non-hypothetical statement of the form xy.{x \nc y.} For example, remember how we wrote a proof-by-contradiction? The same idea is at work here. We want to reach some non-hypothetical conclusion: "When we assume x,{x,} this is what happens. And since this is what happens, it must be true that ..."

Returning to the proof, we are now trying to prove that 1+2++(n+1)=(n+1)(n+2)2.{1 + 2 + \ldots + (n + 1) = \dfrac{(n + 1)(n + 2)}{2}.} We can rewrite this as 1+2++n+(n+1)=(n+1)(n+2)2.{1 + 2 + \ldots + n + (n + 1) = \dfrac{(n + 1)(n + 2)}{2}.} Since we assumed that P(n){P(n)} is true, we know that:

1+2++nn(n+1)2+(n+1) \overbrace{1 + 2 + \ldots + n}^{\dfrac{n(n + 1)}{2}} + (n + 1)

Thus, we have:

n(n+1)2+(n+1)=n2+n+2n+22=n2+3n+22=(n+1)(n+2)2 \begin{aligned} \dfrac{n(n + 1)}{2} + (n + 1) &= \dfrac{n^2 + n + 2n + 2}{2} \\ &= \dfrac{n^2 + 3n + 2}{2} \\ &= \dfrac{(n + 1)(n + 2)}{2} \end{aligned}

Putting this all together:

Let P(n){P(n)} be the proposition that i=1n=n(n+1)2.{\sum_{i = 1}^{n} = \dfrac{n(n + 1)}{2}.} When n=0,{n = 0,} then i=10=0.{\sum_{i = 1}^{0} = 0.} This is the base case. We now prove the inductive case: For n0,{n \geq 0,} P(n)P(n+1).{P(n) \nc P(n + 1).}

Assume P(n){P(n)} is true for purposes of induction. Following this assumption, we must prove that i=1n+1=(n+1)(n+2)2.{\sum_{i = 1}^{n + 1} = \dfrac{(n + 1)(n + 2)}{2}.} Since P(n){P(n)} is true, we can rewrite the expression 1+2++n+(n+1){1 + 2 + \ldots + n + (n + 1)} as n(n+1)2+(n+1).{\dfrac{n(n + 1)}{2} + (n + 1).} Rewriting this expression, we have n2+n+2n+22,{\dfrac{n^2 + n + 2n + 2}{2},} which is n2+3n+22.{\dfrac{n^2 + 3n + 2}{2}.} Factoring this expression, we have (n+1)(n+2)2.{\dfrac{(n + 1)(n + 2)}{2}.}

Thus, we have proved that P(n+1){P(n + 1)} is true. And since P(n+1){P(n + 1)} is true when P(n){P(n)} is true, the implication P(n)P(n+1){P(n) \nc P(n + 1)} cannot be false. Therefore, the implication P(n)P(n+1){P(n) \nc P(n + 1)} must be true. Ergo, nN:(i=1n=n(n+1)2){\forall n \in \nat : \left(\sum_{i = 1}^{n} = \dfrac{n(n + 1)}{2}\right)} is true. {\blacksquare}

Let's do another example. Prove the following:

nN:(3  n3n) \forall n \in \nat: (3 \space\vert\space n^3 - n)

Let's first test the predicate:

n=5:n3n=(5)35=1255=120 n = 5 : n^3 - n = (5)^3 - 5 = 125 - 5 = 120

3 does in fact divide 120.

First, what is our induction hypothesis? It is: Let P(n)=3  n3n{P(n) = 3 \space\vert\space n^3 - n} Next, we should establish that our base case is. Our base case is when n=0.{n = 0.} Checking:

P(0)=(0)30=0 P(0) = (0)^3 - 0 = 0

Our base case is true; 3 does in fact divide 0. Now we turn to the inductive step: For n0,{n \geq 0,} P(n)P(n+1){P(n) \nc P(n + 1)} is true. More formally:

(nNn0):P(n)P(n+1) (\forall n \in \nat \mid n \geq 0) : P(n) \nc P(n + 1)

To prove that this is true, we first assume that P(n){P(n)} is true. In other words, we assume that 3  n3n{3 \space\vert\space n^3 - n} is true. Now we examine the necessary condition, P(n+1).{P(n + 1).} The proposition P(n+1){P(n + 1)} is (n+1)3(n+1).{(n + 1)^3 - (n + 1).} Exampding this:

(n+1)3(n+1)=n3+3n2+3n+1n+1=n3+3n2+2n \begin{aligned} (n + 1)^3 - (n + 1) &= n^3 + 3n^2 + 3n + 1 - n + 1 &= n^3 + 3n^2 + 2n \end{aligned}

Looking at this result, it doesn't really look like n3+3n2+2n{n^3 + 3n^2 + 2n} is a multiple of 3. We need to wrtie this a bit more. We want to use the fact that n3n{n^3 - n} is a multiple of three (remember, we assumed it). Remember, whenever we perform a proof-by-induction, we always want to make use of the sufficient condition. So, to make use of our sufficient condition, we want to get a n{-n} inside the expression. So, we need to rewrite the expression so as to incorporate a minus sign:

(n+1)3(n+1)=n3+3n2+3n+1n+1=n3+3n2+2n=n3n+3n2+3n=(n3n)+3(n2+n) \begin{aligned} (n + 1)^3 - (n + 1) &= n^3 + 3n^2 + 3n + 1 - n + 1 \\ &= n^3 + 3n^2 + 2n \\ &= n^3 - n + 3n^2 + 3n \\ &= (n^3 - n) + 3(n^2 + n) \end{aligned}

Now it's very clear that P(n+1){P(n + 1)} is true:

(n3n)multiple of 3+3(n2+n)multiple of 3 \overbrace{(n^3 - n)}^{\text{multiple of 3}} + \overbrace{3(n^2 + n)}^{\text{multiple of 3}}

We need not always have a base case start at 0. We could have a base case P(b){P(b)} and then the induction step nb:P(n)P(n+1).{\forall n \geq b : P(n) \nc P(n + 1).}

Consider the following problem. We have a 2n×2n{2^n \times 2^n} grid, and we want to tile it with an L-shaped tile, 2×2,{2 \times 2,} such that the entirety of the grid is filled with one square open:

Tiling problem

It looks like we can from the diagram above. Now we want to prove it for all n.{n.} Here is the proposition:

nN,{\forall n \in \nat,} there exists a way to tile a 2n×2n{2^n \times 2^n} region with a center square missing.

First, we establish our induction hypothesis: P(n){P(n) \coloneqq} {\exists} a way to tile a 2n×2n{2^n \times 2^n} region with a center square missing. Second, we establish the base case, P(0.){P(0.)} Where P(0),{P(0),} we only have one square, since 20×20=1.{2^0 \times 2^0 = 1.} That is the center square missing, so P(n){P(n)} is true where n=0;{n = 0;} P(0){P(0)} is true.

Now we consider the inductive case: For n0,{n \geq 0,} assume P(n){P(n)} is true to verify P(n)P(n+1).{P(n) \nc P(n + 1).} Now we must prove that P(n+1){P(n + 1)} is true.

Let's consider 2n+1×2n+1.{2^{n + 1} \times 2^{n + 1}.} It turns out it's very difficult to prove when a center square is missing (try it). It is actually much easier if we make a stronger assumption — any square is missing. With this assumption, we can place the missing square anywhere. In doing so, we can think of any 2n+1×2n+1{2^{n+1} \times 2^{n+1}} region as smaller parts of 2n×2n.{2^n \times 2^n.} And since P(n){P(n)} is true, we can place the missing square anywhere in a region 2n+1×2n+1.{2^{n+1} \times 2^{n+1}.}

Footnotes

  1. The well-ordering principle is often shortened to WOP, not to be confused with Belcalis Marlenis Almánzar and Megan Jovon Ruth Pete's popular hit, WAP.